Pelaksanaan Administrasi Kesiswaan Di MTs Negeri 2 Palembang - Cahaya, Harisma; Setyaningsih, Kris; Rohman, Asep; Kanada, Rabial (PT WIM Solusi Prima, 2024)
This research aims to identify issues in the implementation of student administration at MTs Negeri 2 Palembang, focusing on indicators of coordination, motivation, communication, and direction, as well as supporting and inhibiting factors. This study employs a qualitative descriptive approach, with the main informant being the Head of Administration and supporting informants including the School Principal, Vice Principal of Student Affairs, Teachers, and Students. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and verification techniques, and tested for validity through source and technique triangulation. The results show that student administration can be more effective and efficient by: 1) enhancing coordination not only through meetings but also in daily activities, 2) providing optimal motivation and building morale among administrative staff, 3) ensuring clear and effective communication, and 4) providing easily understandable guidance. Supporting factors for student administration include adequate facilities and infrastructure and good cooperation, while inhibiting factors include students frequently forgetting to bring required administrative documents and a decrease in human resources in the administrative department. Penelitian ini bertujuan untuk mengidentifikasi masalah dalam pelaksanaan administrasi kesiswaan di MTs Negeri 2 Palembang, dengan fokus pada indikator koordinasi, motivasi, komunikasi, dan pengarahan, serta faktor-faktor pendukung dan penghambat. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dengan informan utama Kepala Tata Usaha dan informan pendukung Kepala Sekolah, Waka Kesiswaan, Guru, dan Siswa. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, lalu dianalisis dengan teknik reduksi data, penyajian data, dan verifikasi, serta diuji keabsahannya dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa administrasi kesiswaan bisa lebih efektif dan efisien dengan: 1) meningkatkan koordinasi tidak hanya melalui rapat tetapi juga dalam kegiatan sehari-hari, 2) memberikan motivasi yang optimal dan membangun kepada tenaga administrasi, 3) memastikan komunikasi yang jelas dan baik, dan 4) memberikan pengarahan yang mudah dimengerti. Faktor pendukung administrasi kesiswaan meliputi sarana dan prasarana yang memadai serta kerja sama yang baik, sedangkan faktor penghambatnya adalah siswa sering lupa membawa persyaratan administrasi yang diperlukan dan berkurangnya sumber daya manusia di bagian tata usaha.